(untitled) (International Journal of Occupational Safety and Health, 2026)
Introduction: Occupational noise and vibration are common physical hazards across many industries and are associated with substantial auditory, musculoskeletal, vascular, neurological, and other non‑auditory health effects. This narrative review integrates current evidence to support recognition, assessment, and prevention of these hazards in workplace settings. Methods: A narrative review approach was adopted, consistent with established narrative‑review guidelines and SANRA criteria. Literature searches in major databases focused on occupational noise, hand‑arm and whole‑body vibration, health outcomes, exposure assessment, and prevention. Peer‑reviewed studies, reviews, and authoritative guidelines were included if they addressed exposure characterization, auditory or non‑auditory and musculoskeletal or neurovascular health effects, assessment methods or standards, or engineering, administrative, and personal protective controls. Evidence was synthesized thematically without formal risk‑of‑bias assessment or meta‑analysis. Results: The review indicates that hazardous noise and vibration exposures remain widespread and contribute to noise‑induced hearing loss, cardiovascular and psychological disorders, hand‑arm vibration syndrome, low back pain, and other musculoskeletal and neurovascular conditions. Assessment commonly uses time‑weighted or equivalent continuous sound levels for noise and frequency‑weighted acceleration metrics for vibration, in accordance with international standards and regulations. Multiple engineering, administrative, and personal protective measures are available, but fully integrated workplace programs are still limited. Conclusion: This review provides an occupationally focused framework to strengthen systematic management of combined noise and vibration hazards.